Juridical Analysis of Stock Market Response to Government Economic Policy: The Case of Declining IHSG in Indonesia - Salmon, Harly Cliford Jonas (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Acroeconomic changes in Indonesia have a significant impact on the industrial sector and capital markets. High inflation, the depreciation of the rupiah, and rising interest rates can reduce purchasing power and corporate profitability, ultimately leading to a decline in the Composite Stock Price Index (IHSG). This economic instability may prompt investors to withdraw their capital from the stock market, further worsening the IHSG condition.Purposes of the Research: This study aims to analyse how government economic policies influence IHSG movements by examining market responses to the fiscal and monetary policies implemented by the Indonesian government.Methods of the Research: This research adopts a normative juridical approach by analysing laws and legal norms related to economic policies. The study examines regulations affecting stock market stability and their impact on investment decisions.Findings of the Research: The findings indicate that unclear fiscal and monetary policies negatively affect IHSG. The 5% decline in IHSG on March 18, 2025, reflects economic and political uncertainty, causing investors to be more cautious. Policies such as budget cuts for ministries and the free nutritious meal program have triggered negative market reactions. Additionally, inconsistent tax policies have further increased economic uncertainty. This study concludes that transparency and policy consistency are crucial in maintaining IHSG stability and enhancing investor confidence in Indonesia’s capital market.